Development of Large-Scale Functional Brain Networks in Children - Supekar, Kaustubh; Musen, Mark; Menon, Vinod (PLOS Biology, 2009)
Large-scale rewiring of brain circuits in children leads to emergence of hierarchical organization in the mature adult brain.